PENGUKURAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MELALUI IMPLEMENTASI MODEL PEMBELAJARAN KNISLEY BERBASIS GAYA BELAJAR - Irsyadatul Mahmudah; Siti Munawarroh; Ainur Rosikin; Abdul Halim Fathani (Faculty of teaching training and education, 2018)
AbstrakTujuan penelitian ini untuk mengetahui ada atau tidaknya perbedaan yang signifikan antara kemampuan pemahaman konsep siswa yang mengikuti model pembelajaran matematika Knisley (MPMK) berdasarkan gaya belajar dengan kemampuan pemahaman konsep siswa yang mengikuti pembelajaran konvensional, serta mendeskripsikan kemampuan pemahaman konsep siswa yang mengikuti model pembelajaran matematika Knisley (MPMK) berdasarkan gaya belajar dan kemampuan pemahaman konsep siswa yang mengikuti pembelajaran konvensional. Penelitian ini dilakukan di SMP Islam 01 Batu, Kelas VII pada materi segiempat dengan sampel 23 siswa sebagai kelas eksperimen dan 23 siswa kelas kontrol. Metode pengumpulan data yang digunakan adalah metode tes yang terdiri dari pretest dan posttest kemampuan pemahaman konsep, serta angket gaya belajar. Analisis data dalam penelitian ini adalah dengan menggunakan uji normalitas, uji homogenitas dan uji two-way ANOVA. Berdasarkan hasil analisis data penelitian kuantitatif menunjukkan bahwa terdapat perbedaan antara kemampuan pemahaman berdasarkan gaya belajar antara siswa yang mengikuti model pembelajaran matematika Knisley (MPMK) dengan siswa yang mengikuti model pembelajaran konvensional. Sedangkan hasil data penelitian kualitatif diperoleh kemampuan pemahaman konsep berdasarkan gaya belajar auditorial untuksiswa yang mengikuti model pembelajaran matematika Knisley (MPMK) lebih baik dibandingkan kemampuan pemahaman konsep berdasarkan gaya belajar visual dan kinestetik.Ã‚Â Kata Kunci : Pemahaman Konsep Matematika, Model Pembelajaran Knisley, Gaya BelajarMEASUREMENT OF ABILITY OFÃ‚Â CONCEPTUAL UNDERSTANDING IN MATHEMATICS THROUGH THE IMPLEMENTATION OF KNISLEY LEARNING MODEL BASED ON LEARNING STYLESÃ‚Â AbstractThis research is motivated by the low ability of understanding the concept of students and the use of the model given by the teacher is still less effective because the applied learning model is still centered on the teacher that is conventional learning. The purpose of this study is to determine whether or not there is a significant difference between the ability to understand the concepts of students who follow the model of learning mathematics Knisley based on learning styles with the ability to understand the concept of students who follow conventional learning, and describes the ability to understand the concept of students who follow the model of learning mathematics Knisley based on learning styles and students' conceptual understanding abilities that follow conventional learning. This research was conducted in Islamic Junior High School 01 Batu, Class VII in quadrilateral material with sample of 23 students as experiment class and 23 students of control class. Data collection method used is a test method that consists of pretest and posttest the ability to understand the concept, as well as questionnaire learning style. Data analysis in this research is by using normality test, homogeneity test and two-way ANOVA test. Based on the results of quantitative research data analysis shows that there is a difference between the ability of understanding based on learning styles between students who follow the model of learning mathematics Knisley with students who follow the conventional learning model. While the results of qualitative research data obtained the ability to understand the concept based on auditorial learning style for students who follow the model of learning mathematics Knisley better than the ability to understand the concept based on visual and kinesthetic learning styleÃ‚Â Keywords: Understanding Mathematical Concepts, Knisley Learning Model, Learning Styles